Revisiting False-Positive and Imitated Dissociative Identity Disorder - Pietkiewicz, Igor Jacob; Bańbura-Nowak, Anna; Tomalski, Radosław; Boon, Suzette (Frontiers in Psychology, 2021)
ICD-10 and DSM-5 do not provide clear diagnosing guidelines for DID, making it difficult to distinguish ‘genuine’ DID from imitated or false-positive cases. This study explores meaning which patients with false-positive or imitated DID attributed to their diagnosis. 85 people who reported elevated levels of dissociative symptoms in SDQ-20 participated in clinical assessment using the Trauma and Dissociation Symptoms Interview, followed by a psychiatric interview. The recordings of six women, whose earlier DID diagnosis was disconfirmed, were transcribed and subjected to interpretative phenomenological analysis. Five main themes were identified: (1) endorsement and identification with the diagnosis. (2) The notion of dissociative parts justifies identity confusion and conflicting ego-states. (3) Gaining knowledge about DID affects the clinical presentation. (4) Fragmented personality becomes an important discussion topic with others. (5) Ruling out DID leads to disappointment or anger. To avoid misdiagnoses, clinicians should receive more systematic training in the assessment of dissociative disorders, enabling them to better understand subtle differences in the quality of symptoms and how dissociative and non-dissociative patients report them. This would lead to a better understanding of how patients with and without a dissociative disorder report core dissociative symptoms. Some guidelines for a differential diagnosis are provided.